Transplacental Passage of Vancomycin in the ex vivo Human Perfusion Model - Michael D. Hnat; Julie Gainer; Roger E. Bawdon; George D. Wendel (Hindawi Limited, 2004)
Objectives: To determine maternal-fetal transplacental passage of vancomycin in the ex vivo human placental perfusion model.